Immune check point inhibitors in BRAF mutated metastatic colorectal cancer: A review - Alfredo Colombo; Stefano Cordio; Concetta Maria Porretto (Society of Gastrointestinal Intervention, 2024)
Metastatic colorectal cancers with BRAF mutation are a class of tumors that have a poor prognosis compared to wild type patients. Even if this group has found some hope in targeted therapy with multi-targeted blockade of the mitogen-activated protein kinase (MAPK) signalling pathway, more work must be done to increase treatment efficacy, particularly for the microsatellite stability/DNA proficient mismatch repair (MSS/pMMR) subtype. Patients with BRAF mutant colorectal cancer and high microsatellite instability/DNA deficient mismatch repair (MSI-H/dMMR) are considered to have a high tumor mutation load and a lot of neoantigen, which makes immunotherapy likely to be effective. It is generally accepted that MSS/pMMR colorectal cancer is an immunologically "cold" tumor that is resistant to immunotherapy. Then, patients with BRAF mutant colorectal cancer appear to find hope with targeted therapy paired with immune checkpoint blockade therapy. The clinical effectiveness and developing new approaches of immune checkpoint blockade therapy for MSI-H/dMMR and MSS/pMMR BRAF mutant metastatic colorectal cancer are reviewed in this paper. We also address possible biomarkers in the tumor immune microenvironment for predicting immunotherapeutic response in BRAF mutant colorectal cancer.